A finite element approach for predicting the ultimate rotation capacity of RC beams - Rodrigues, Eduardo A.; Manzoli, Osvaldo L. [UNESP]; Bittencourt, Túlio N.; Bitencourt Jr., Luís A.G.; Dos Prazeres, Plínio G.C. (My University, 2013)
This paper presents a numerical approach to model the complex failure mechanisms that define the ultimate rotational capacity of reinforced concrete beams. The behavior in tension and compression is described by a constitutive damage model derived from a combination of two specific damage models [1]. The nonlinear behavior of the compressed region is treated by the compressive damage model based on the Drucker-Prager criterion written in terms of the effective stresses. The tensile damage model employs a failure criterion based on the strain energy associated with the positive part the effective stress tensor. This model is used to describe the behavior of very thin bands of strain localization, which are embedded in finite elements to represent multiple cracks that occur in the tensioned region [2]. The softening law establishes dissipation energy compatible with the fracture energy of the concrete. The reinforcing steel bars are modeled by truss elements with elastic-perfect plastic behavior. It is shown that the resulting approach is able to predict the different stages of the collapse mechanism of beams with distinct sizes and reinforcement ratios. The tensile damage model and the finite element embedded crack approach are able to describe the stiffness reduction due to concrete cracking in the tensile zone. The truss elements are able to reproduce the effects of steel yielding and, finally, the compressive damage model is able to describe the non-linear behavior of the compressive zone until the complete collapse of the beam due to crushing of concrete. The proposed approach is able to predict well the plastic rotation capacity of tested beams [3], including size-scale effects.
Keywords: Damage model; Nonlinear analysis; Reinforced concrete; Rotation capacity; Size-scale effects; Drucker-prager criterions; Finite-element approach; Plastic rotation capacity; Reinforced concrete beams; Tension and compression; Concrete beams and girders; Concrete buildings; Concrete construction; Concretes; Cracks; Forecasting; Fracture mechanics; Trusses; Finite element method